Using Social Network to Support Smart City Initiatives - Figueredo, Mickael; Ribeiro, José Lucas; Emanuel, Arthur; Cacho, Andréa; Farias, Hiarley; Coelho, Jazon; Prolo, Carlos; Cacho, Nélio (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2015: Proceedings of the 21st Brazilian Symposium on Multimedia and the Web, 2015)
A central issue in the context of smart cities is for one to be able to acquire timely information about city events for purposes ranging from being able to act promptly in response to events to just monitoring and collecting statistics about them. This paper describes an initial framework focused on processing messages posted in the Twitter social network. Key issues are the high throughput – a large volume of data per second that needs to be processed, and the need to process ill formed natural language texts. With these in mind the framework has pipelined modules for robust, fast, real time tweet acquisition and storage, filtering of several kinds, natural language processing and sentiment analysis, that feed a final analysis and visualization module. A case study of sentiment analysis during the FIFA World Cup 2014 in Brazil is used to validate the effort made so far.